On the effect of the number of annual growth rings, specific gravity and temperature on redwood elastic modulus - T.Mascia, Nilson; M.Cramer, Steven (Maderas. Ciencia y Tecnología, 2014)
Due to the natural origin of wood, physical parameters such as speciﬁ c gravity and the number of growth rings per inch affect its properties. In this study, to evaluate the effect that these physical para-meters have on the elastic properties of wood, particularly on elastic modulus, a uniaxial compression test was performed on specimens. These specimens consisted of solid cubes of the Redwood species of wood with a width of 10.16 cm. Three different temperature conditions—ambient temperature (18°C), cold temperature (-28°C) and hot temperature (65°C) were used to carry out the tests. Speciﬁ c gravity ranged from 0.29 to 0.45, and the number of growth rings per inch varied from 2 to 24 rings per inch. The minimum moisture content in the specimens was 2%, and reached a maximum of 16% according to the temperature conditions. The results from the statistical analysis indicated that the effect that the number of growth rings per inch has on elastic modulus is more signiﬁ cant than the effects of speciﬁ c gravity or even of temperature. As a consequence, we suggest that the number of growth rings per inch can be used as a predictor for wood elastic modulus. Debido al origen natural de la madera, parámetros físicos como la gravedad especíﬁ ca y el núme-ro de anillos de crecimiento afectan sus propiedades. En este estudio para evaluar el efecto que estos parámetros físicos tienen sobre las propiedades elásticas de la madera, particularmente en el módulo de elasticidad, ensayos de compresión uniaxial se realizaron en probetas normalizadas. Estos probetas consistieron en cubos sólidos de la especie de madera Redwood con arista de 10,16 cm. Tres diferentes condiciones de temperatura fueron utilizadas para llevar a cabo las pruebas: ambiente (18 °C), bajo cero (-28 °C) y temperado (65 °C). La gravedad especíﬁ ca osciló entre 0,29 a 0,45 y el número de anillos de crecimiento varió de 2 a 24 anillos por pulgada. El mínimo contenido de humedad en las muestras fue del 2% y alcanzó un máximo del 16% de acuerdo a las condiciones de temperatura. Los resultados del análisis estadístico indicaron que el efecto del número de anillos de crecimiento por pulgada es más importante que los efectos de la gravedad especíﬁ ca o incluso que el de la temperatura sobre el módulo de elasticidad. En consecuencia, se sugiere aquí que el número de anillos de crecimiento por pulgada pueda ser utilizado como predictor del módulo de elasticidad de la madera.